Increased respiratory chemosensitivity induced by infusing almitrine intravenously in healthy man. Issue 3 (March 1983) - Stanley, N N; Galloway, J M; Gordon, B; Pauly, N
Abstract : The respiratory effects of intravenously infused almitrine were evaluated in healthy volunteers. In the dose range 0.25-1.0 mg/kg/hour it caused large and dose-dependent increases in hypoxic chemosensitivity, which were longlasting and more persistent than the drug's retention in the plasma. Increases in sensitivity to hypercapnia were much less and were detected only when the plasma almitrine exceeded 200 ng/ml. Small increases in resting ventilation and metabolic rate with a decrease in mixed venous carbon dioxide tension occurred only at the highest infusion rate. The findings accord with an action of almitrine in the peripheral chemoreceptors, which may be of therapeutic value in managing some cases of respiratory failure.